2021
DOI: 10.1002/aur.2555
|View full text |Cite
|
Sign up to set email alerts
|

An elevated anxiety level among prepubertal autistic boys with non‐treatment‐seeking functional gastrointestinal disorders: A case–control study

Abstract: Children with autism commonly suffer from comorbid functional gastrointestinal disorders (FGID) and anxiety. The raised prevalence of both conditions in autism suggests complex reciprocal relationships, which are seldom explored in non-treatment-seeking FGID. The relationships between subtypes of FGID and anxiety are also unclear. This study recruited boys with autism and age-matched typically developing (TD) boys, aged 4-11 years, who were not actively seeking help for gastrointestinal problems. Their parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Furthermore, autistic symptoms (AQ-10), anxiety (SCAS-P) and overall psychopathology (SDQ) levels were highest among the ASD FGID+ and explorative analyses also showed that lower alpha diversity and microbiota composition at the phylum level (F:B ratio) correlated with higher SDQ and AQ-10. Our results thus corroborated the reported potential correlations between microbiota, GI and neuropsychiatric symptoms in ASD [10][11][12] . Notwithstanding the rigorous attempts made to control for possible confounders and optimize the characterization of psychopathology and FGIDs in this study, our findings should be interpreted from the wider perspective of mixed results in published studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, autistic symptoms (AQ-10), anxiety (SCAS-P) and overall psychopathology (SDQ) levels were highest among the ASD FGID+ and explorative analyses also showed that lower alpha diversity and microbiota composition at the phylum level (F:B ratio) correlated with higher SDQ and AQ-10. Our results thus corroborated the reported potential correlations between microbiota, GI and neuropsychiatric symptoms in ASD [10][11][12] . Notwithstanding the rigorous attempts made to control for possible confounders and optimize the characterization of psychopathology and FGIDs in this study, our findings should be interpreted from the wider perspective of mixed results in published studies.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the gut microbiome could contribute to the pathogenesis of ASD. Furthermore, as ASD children with comorbid FGID have a higher severity of rigid-compulsive behavior 10 , sensory over-responsivity 11 , and anxiety, even at prepubertal ages 12 , the altered gut microbiome in FGID may also mediate neuropsychiatric and behavioral symptoms.…”
mentioning
confidence: 99%
“…Children with ASD are more likely to experience constipation than TD children ( Supplementary Figure S2 , see the Supplementary Material ). Twelve articles ( 19 , 21 , 22 , 24 , 25 , 32 , 34 37 , 39 , 41 ) recorded cases of children with ASD complaining of simple abdominal pain. Seven studies ( 18 , 18 , 20 , 23 , 29 , 30 , 38 ) reported cases of defecation-related abdominal pain, and two ( 26 , 28 ) found no abdominal pain.…”
Section: Resultsmentioning
confidence: 99%
“…All 25 articles provided information on constipation in children with ASD, with an prevalence of 37% (95% CI: 0.30, 0.43), I 2 = 96.00%, p = 0.00 ( Supplementary Figure S7 , see the Supplementary Material ). A total of 22 articles ( 18 27 , 29 32 , 34 37 , 39 41 ) documented diarrhea in children with ASD, with a combined prevalence of 19% (95% CI: 0.14, 0.24), I 2 = 96.86%, p = 0.00 ( Supplementary Figure S8 , see the Supplementary Material ). Data on abdominal pain in children with ASD were reported in 21 articles ( 18 26 , 28 30 , 32 , 34 37 , 39 , 41 ), with an prevalence of 21% (95% CI: 0.14, 0.28), I 2 = 96.55%, p = 0.00 ( Supplementary Figure S9 , see the Supplementary Material ).…”
Section: Resultsmentioning
confidence: 99%
“…We may also cite changes in the facial muscles seen in this group, which may contribute to the establishment of harmful oral habits 25,28 . However, other factors can influence the occurrence of bruxism in individuals with ASD, such as anxiety, 29–32 stress 29 and the side effects of continuous‐use medications, which can have repercussions for the oral cavity 25,28 …”
Section: Discussionmentioning
confidence: 95%